Baseball as a road to God : seeing beyond the game - Sexton, John (Gotham Books, 2013)
Applying to the secular activity of baseball a form of inquiry usually reserved for the study of religion, Sexton reveals a surprising amount of common ground between the game and what we all recognize as religion: sacred places and time, faith and doubt, blessings and curses, and more.